2020
DOI: 10.1097/ta.0000000000002786
|View full text |Cite
|
Sign up to set email alerts
|

Rescue therapy for severe COVID-19–associated acute respiratory distress syndrome with tissue plasminogen activator: A case series

Abstract: Conflicts of Interest: CDB, HBM, EEM, and MBY have patents pending related to both coagulation/fibrinolysis diagnostics and therapeutic fibrinolytics, and are passive co-founders and holds stock options in Thrombo Therapeutics, Inc. HBM and EEM have received grant support from Haemonetics and Instrumentation Laboratories. MBY has previously received a gift of Alteplase (tPA) from Genentech, and owns stock options as a co-founder of Merrimack Pharmaceuticals. All other authors have nothing to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…The current explanations for the elevated D-dimer in critically ill patients are multiple, including "suppression of fibrinolysis", "secondarily hyperactive fibrinolysis", "consumption of fibrinolysis", "fibrinolysis resistance", and "fibrinolysis shutdown" 21,22 . To address the coagulopathic changes complicating COVID-19, two diametrically different therapeutic regimes are in practice: fibrinolytic (alteplase-tPA) 10,11,[23][24][25][26][27][28] and antifibrinolytic therapies (nafamostat and tranexamic acid (TXA)) [29][30][31] . It is therefore imperative to clarify the role of pathophysiologic derangements of fibrinolysis in clinical outcomes that occur in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The current explanations for the elevated D-dimer in critically ill patients are multiple, including "suppression of fibrinolysis", "secondarily hyperactive fibrinolysis", "consumption of fibrinolysis", "fibrinolysis resistance", and "fibrinolysis shutdown" 21,22 . To address the coagulopathic changes complicating COVID-19, two diametrically different therapeutic regimes are in practice: fibrinolytic (alteplase-tPA) 10,11,[23][24][25][26][27][28] and antifibrinolytic therapies (nafamostat and tranexamic acid (TXA)) [29][30][31] . It is therefore imperative to clarify the role of pathophysiologic derangements of fibrinolysis in clinical outcomes that occur in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…62 Indeed, some groups have published case series for patients with COVID-19 ARDS who were treated with salvage antithrombolytic agents. [63][64][65] All patients had some level of improvement in oxygenation and/or hemodynamics after the administration of tissue plasminogen activator, but in most cases, patients ultimately died. Nonetheless, the scientific rationale for using fibrinolytic therapy in COVID-19 ARDS-namely, the consistent findings of pulmonary microvascular thrombosis-has resulted in the initiation of urgently needed clinical trials studying the role of antithrombotic agents in COVID-19 ARDS.…”
Section: Anticoagulation and Thrombolyticsmentioning
confidence: 99%
“…All the 3 patients demonstrated improvement in their oxygenation after initiation of tPA therapy. Barrett and colleagues 44 used tPA and heparin in 5 COVID-19 infected patients with refractory respiratory failure and thrombotic coagulopathy. The authors reported that these 3 patients had sustained improvements after fibrinolytic therapy (including 1 patient extubated 7 days post-tPA), while the other 2 had non-sustained improvements (1 patient remained mechanically ventilated and 1 patient died from multi-organ failure).…”
Section: Thromboembolismmentioning
confidence: 99%
“…The authors reported that these 3 patients had sustained improvements after fibrinolytic therapy (including 1 patient extubated 7 days post-tPA), while the other 2 had non-sustained improvements (1 patient remained mechanically ventilated and 1 patient died from multi-organ failure). 44 Though not yet reported in the context of COVID-19 lung disease, nebulized tPA is an attractive option for selective pulmonary fibrinolysis with fewer systemic bleeding risks. 30 Further investigation with controlled studies and larger patient groups are needed in order to determine the efficacy and safety of anticoagulation and fibrinolytic therapies use in this context.…”
Section: Thromboembolismmentioning
confidence: 99%